Mythological Foundations of Highland Festivals: The Case of The Kadırga Otcu Festival - Mutlu Kaya; Cevdet Yılmaz (Coğrafya Dergisi)
High places have created a sense of respect and trust in people throughout history, and the ancient Turks also gave special importance to mountains due to their majestic appearance and proximity to the sky. The waters of the mountains, which were seen as the seat of God, were considered sacred, reaching them was found valuable, and sacrifices were offered to God. These beliefs were also carried to Anatolia with the Turks, and although some changes were observed under the influence of Islam, the meaning attributed to the mountains continued. Some of these beliefs still exist in the lives of the Turks, who have moved between the highland and winter residences in the Black Sea Mountains for the purpose of animal husbandry for centuries. The study aims to reveal that the highland festivals are ceremonies that include mythological elements rather than rural entertainment with the example of the Kadırga Otçu Festival. In the research, data obtained from in-depth interviews with local people, horon (a folkloric dance) trainers, local artists and local association managers were used by using a semi-structured interview form. It has been determined that the Kadırga Otçu Festival is a ceremony with mythological rituals that was born in the light of the ancient belief systems of the Turks, reorganized in the Islamic framework in Anatolia, and still maintains its ties with the past beliefs.